IMPLEMENTASI ADAB MEMBACA DAN MENGHAFAL AL-QUR’AN TERHADAP SISWA DALAM PEMBENTUKAN KARAKTER QUR’ANI: (Studi Deskriptif di Sekolah Islam Qothrun Nada) - Umi Hasanah; Taufiq Fauzan Ginanjar (CV. Lafadz Jaya, 2026)
In today's era, with the rapid development of technology and culture, while it has significantly contributed to the advancement of globalization, many have also become problems for the current generation. In this regard, the application of religious values is actually very helpful in increasing understanding in daily life. As Muslims, we should be concerned about this issue. Therefore, the purpose of this journal is to support the implementation of noble etiquette for students at Qothrun Nada Islamic School. Therefore, the title